Studies on the mechanism of non-visualization of diseased human gallbladders during oral cholecystography. Issue 758 (December 1988) - Jacyna, M. R.; Ross, P. E.; Hopwood, D.; Bouchier, I. A.
Abstract : Oral cholecystography is a well established method for studying the human gallbladder and radiological non-visualization of the gallbladder has been shown to correlate highly with the presence of disease. The exact mechanism by which diseased gallbladders fail to visualize is unclear, but may be due to a failure of the gallbladder to concentrate the luminal contents. Concentration of gallbladder contents is achieved by the reabsorption of water, the driving force for which is active sodium (Na+) absorption. Therefore Na+ transport was studied by measuring the flux of Na22 across isolated human gallbladder mucosa (obtained at cholecystectomy) and compared with the results of oral cholecystography and histological grading. In 27 gallbladders studied, 59% absorbed Na+, whilst the remainder secreted Na+. Comparison with histological grading showed that as gallbladders became more diseased they absorbed less Na+ and were more likely to secrete Na+. In addition, gallbladders that absorbed Na+ were significantly more likely to visualize on cholecystography than those that secreted Na+. These results indicate that some diseased human gallbladders secrete, rather than absorb, Na+ and suggest that the mechanism for radiological non-visualization is failure of fluid absorption and the development of active fluid secretion.